2007
DOI: 10.1518/001872007x230208
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visual Display Distance on Eye Accommodation, Head Posture, and Vision and Neck Symptoms

Abstract: The location of a computer display should take into account the size of the characters on the screen and the visual acuity of the user.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 19 publications
4
62
1
1
Order By: Relevance
“…25 In a study of the effects of visual display distance on eye accommodation, head posture, and vision and neck symptoms in computer users, the optimal distance was between near (52 cm) and middle (73 cm) distance from the eyes (taking into account screen-font size and the subject visual acuity). 40 A study of optimal viewing distance among 14 surgeons during simulated laparoscopic surgery that used a 34-cm cathode-ray-tube monitor (14-inch diagonal) concluded that the optimal distance was between 90 and 182 cm for close-up viewing (defined as the minimum view distance below which image degradation was experienced) and 139 to 303 cm for maximal distance viewing (defined as the maximal distance at which the finest details of an image could still be seen). 41 Taken together, we estimate that the optimal viewing distance of video monitors during endoscopy is between 52 and 182 cm.…”
Section: Optimizing the Ergonomics Of Endoscopymentioning
confidence: 99%
“…25 In a study of the effects of visual display distance on eye accommodation, head posture, and vision and neck symptoms in computer users, the optimal distance was between near (52 cm) and middle (73 cm) distance from the eyes (taking into account screen-font size and the subject visual acuity). 40 A study of optimal viewing distance among 14 surgeons during simulated laparoscopic surgery that used a 34-cm cathode-ray-tube monitor (14-inch diagonal) concluded that the optimal distance was between 90 and 182 cm for close-up viewing (defined as the minimum view distance below which image degradation was experienced) and 139 to 303 cm for maximal distance viewing (defined as the maximal distance at which the finest details of an image could still be seen). 41 Taken together, we estimate that the optimal viewing distance of video monitors during endoscopy is between 52 and 182 cm.…”
Section: Optimizing the Ergonomics Of Endoscopymentioning
confidence: 99%
“…Professional use of modern instruments of Information or Communication Technology (ICT) is linked with eye-neck/scapular area problems (Treaster et al 2006;Rempel et al 2007;Wiholm et al 2007;Helland et al 2008;Torii et al 2008;Ukai and Howarth 2008;Tornqvist et al 2009). Understanding the causes of these lingering work-environment problems remains a major scientific goal (Lie and Watten 1987;Franzén et al 2000;Piccoli 2003;Sjøgaard et al 2006;Mathiassen 2006;Strøm et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the injuries of the musculoskeletal system have a multifactorial etiology [5]. The complaints in the region of the back are linked mainly to work posture, nonergonomic work organization, inadequate duration and problems in organization of the work tasks [13], while the ones in the region of the neck -with non-ergonomic work posture, the presence of uncorrected refractional abnormalities, and strain [9]. Prolonged musculoskeletal sickness absence was found to be more frequent in groups with greater time pressure at work, lower job control and more adverse beliefs about the work-relatedness of musculoskeletal disorders [1].…”
Section: Discussionmentioning
confidence: 99%